Ancestral recall : the Celtic revival and Japanese modernism - Hart, Aoife Assumpta (McGill-Queen's University Press, 2016)
"Despite distance and differences in culture, the early twentieth century was a time of literary cross-pollination between Ireland and Japan. Notably, the Irish poet and playwright William Butler Yeats had a powerful influence on Japanese letters, at the same time that contemporary and classical Japanese literature and theatre impacted Yeats's own literary experiments. Citing an extraordinary range of Japanese and Irish texts, Aoife Hart argues that Japanese translations of Irish Gaelic folklore and their subsequent reception back in Ireland created collisions, erasures, and confusions in the interpretations of literary works. Assessing the crucial roles of translation and transnationalism in cross-cultural exchanges between the Celtic Revival and Japanese writers of the modern period, Hart proves that interlingual dialogue and folklore have the power to reconstruct a culture's sense of heritage. Rejecting the notion that the Celtic Revival was inward and parochial, Hart suggests that, seeking to protect their heritage from the forces of globalization, the Irish adapted their understanding of heritage to one that exists within the transnational contexts of modernity--a heritage that is locally produced but internationally circulated. In doing so, Hart maintains that the cultural contact and translation between the East and West traveled in more than one direction: it was a dialogue presenting modernity's struggles with cosmopolitanism, gender, ethnic identity, and transnationalism. An inspired exploration of transpacific literary criticism, Yeats scholarship, and twentieth-century Japanese literature, Ancestral Recall tracks the interplay of complex ideas across languages and discourses."--